2008
DOI: 10.1016/j.neuroimage.2007.07.063
|View full text |Cite
|
Sign up to set email alerts
|

BOLD study of stimulation-induced neural activity and resting-state connectivity in medetomidine-sedated rat

Abstract: Functional magnetic resonance imaging (fMRI) in anesthetized-animals is critical in studying the mechanisms of fMRI and investigating animal models of various diseases. Medetomidine was recently introduced for independent anesthesia for longitudinal (survival) fMRI studies in rats. Since stimulation-induced fMRI signal is anesthesia-dependent and its characteristics in rats under medetomidine are not fully elucidated, the blood oxygenation level dependent (BOLD) fMRI response to electrical forepaw stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
181
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(216 citation statements)
references
References 67 publications
(102 reference statements)
31
181
4
Order By: Relevance
“…Dexmedetomidine, an α 2 -agonist routinely used in human medical practice, produces dose-dependent sedative effects along with analgesia, muscle relaxation, and anxiolysis. It was recently introduced for longitudinal functional MRI and resting state fMRI studies in rodents (15,52). However, the sedative effect of medetomidine is reduced with constant infusion of medetomidine alone, and a stepwise dose increase has been suggested to maintain stable sedation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, an α 2 -agonist routinely used in human medical practice, produces dose-dependent sedative effects along with analgesia, muscle relaxation, and anxiolysis. It was recently introduced for longitudinal functional MRI and resting state fMRI studies in rodents (15,52). However, the sedative effect of medetomidine is reduced with constant infusion of medetomidine alone, and a stepwise dose increase has been suggested to maintain stable sedation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Nociceptive stimuli have been shown to reliably evoke this intriguing negative fMRI responses in the rat striatum under alphachloralose anesthesia, 2,5,6,10 medetomidine sedation, 4 or medetomidine combined with light isoflurane (0.4%) anesthesia. 3 This stimulation model has potential to serve as a functional imaging marker for striatal functional integrity for various types of preclinical applications in rodents.…”
Section: Introductionmentioning
confidence: 98%
“…1 It plays a pivotal role in several neurodegenerative disorders and regulating motor behavior. Recent reports showed that unilateral noxious forepaw electrical stimulation in rats evoked sustained negative blood oxygenation level dependent (BOLD), cerebral blood flow (CBF), and cerebral blood volume (CBV) functional magnetic resonance imaging (fMRI) responses in the bilateral striatum with no significant difference between two hemispheres, [2][3][4][5][6] while the neuronal spike and c-Fos activities increased. 6 This negative response has also been observed in epileptic rats during whisker stimulation 7 or normal rats during direct nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensory and motor areas are strongly connected across hemispheres via the corpus callosum and exhibit high BOLD correlation when typical ''steady-state'' analysis methods are used (Pawela et al, 2008;Williams et al, 2010;Zhao et al, 2008). In contrast, the left and right caudate putamen (CP) are only indirectly connected but still exhibit BOLD-based functional connectivity (Williams et al, 2010;Zhao et al, 2008). The caudate also receives input from somatosensory cortex, but a signal from the two areas is usually not correlated in functional connectivity studies.…”
Section: Introductionmentioning
confidence: 99%